Technical and Economical Assessment of SO3/SO2 Removal from Sulphuric Acid Plants in a Petrochemical Industry and Conversion to Ammonium Sulfate - ATABI, FARIDEH; ATAEI*, ABTIN; SHAFIZADEH, S. (Asian Journal of Chemistry, 2009)
In the present study, various methods to control sulfur oxides emission from stacks of sulfuric acid production plants have been investigated. Considering their advantages and disadvantages, functional conditions and the amount of sulfur oxides removal, the researchers investigated various catalytic methods of sulfur oxides removal by flue gas desulphurization methods. Flue gas desulphurization (FGD) processes received more attention due to using dry washing and producing recyclable products which can be utilized to produce useful products to compen-sate for some part of the capital cost. Among these methods, two of which were chosen for this study. The first method was desulphurization by ammonia (Plant A) and the second one was a combination of the first method and dry scrubbing process with calcium hydroxide as the sorbent material (Plant B). Simulation of the systems was carried out through HYSYS v3.1 software. As the technical functions of both of the methods in removal of sulfur oxides were nearly the same, they were compared to each other from the economic point of view. As removal of sulfur oxides was nearly the same (110 tones daily) in both methods, the external costs of production reduction of SOX as a pollutant substance is the same. Therefore, economic index of these two methods were calcul-ated through COMFAR III software. Consequently, the more economical method for desulphurization of sulfuric acid production plants has been chosen.